Some Effects of Unemployment on the Health of Unemployed Quebec Workers - Soderstrom, Lee (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
The author estimates the effect of being unemployed on the health of unemployed Quebec workers. The results imply that the health effects are heterogenous, at least for unemployed men and women.